Pengembangan Model AHP-Topsis Terintegrasi untuk Penilaian Pemasok Alat Konstruksi - Rigel Pawallo; Mega Waty (Departement of Civil Engineering, Universitas Winaya Mukti, 2026)
The selection of construction equipment suppliers heavily impacts project quality and supply chain sustainability. The research gap addressed here is that previous studies rarely integrate operational procurement metrics with global sustainability standards. This study fills this gap by developing an integrated AHP-TOPSIS multi-criteria decision-making model for PT Gamila Buana Nusantara. Pairwise-comparison data were obtained from 3 experts directly involved in the company's procurement process—specifically a Procurement Manager, a Senior Buyer, and a Supply Chain Specialist — each with 10 years of professional experience, selected through purposive sampling. The AHP method determines priority weights, while TOPSIS ranks alternative suppliers. Results show that quality, price, and delivery are the main criteria. The novelty of this study lies in bridging internal corporate operational evaluation directly with Sustainable Development Goals (SDG 9) frameworks, providing a highly systematic and transparent model. This study contributes to SDG 9 (Industry, Innovation, and Infrastructure) by strengthening resilient infrastructure, value chain management, and process innovation in the construction equipment procurement system.